LEADERSHIP AND ISLAM WASATHIYAH PERSPECTIVE OF THE QUR'AN, HADITHS AND 'ULAMA - Sumarto Sumarto; Ahamad Faosiy Ogunbado (International Journal of Southeast Asia, 2021)
This paper discusses Leadership and Islam Wasathiyah Perspective of The Qur'an, Hadith and 'Ulama. The leadership displayed by a leader is an implication of his ability to manage his emotional intelligence and spiritual intelligence. Goleman in Abd. Kadim Masaong said that optimizing the management of emotional intelligence will produce four competency domains that are very effective in creating a leadership style, namely, the domains of selfawareness, self-management, social awareness and relationship management. Tawassuth is an attitude that is in the middle or between two attitudes, namely not too far to the right (fundamentalist) and too far to the left (liberalist). With this tawassuth attitude, Islam will be easily accepted in all walks of life. The character of tawassuth in Islam is the middle point between the two ends and it is a virtue that has been placed by Allah Subhana wata'ala from the start. The value of tawassuth, which has become a principle in Islam, needs to be applied in all fields so that the religion of Islam and the religious expressions of Muslims become witnesses of measuring the truth for all human attitudes and behavior in general.